2016
DOI: 10.19090/pp.2016.2.199-217
|View full text |Cite
|
Sign up to set email alerts
|

Dva Tipa Ličnosti Među Osuđenicima: Razlike U Psihopatiji, Agresivnosti I Krivičnim Delima

Abstract: Cilj ovog istraživanja je ispitivanje klasifikacije osuđenika na osnovu osobina ličnosti. Na uzorku od 166 muškaraca lišena slobode, osuđena za nasilna krivična dela, primenjena je skraćena verzija upitnika Velikih pet plus dva (VP+2-70), Upitnik za procenu psihopatije (PAQ) i Upitnik agresivnosti BODH. Rezultati analize latentnih profila pokazuju da se na osnovu VP+2-70 mogu identifikovati dve klase osuđenika – klasa agresivnih i klasa emocionalno stabilnih osuđenika. Pri tome, osnovna razlika između klasa je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Juvenile delinquents display high neuroticism and low conscientiousness (Kodžopeljić et al, 2014), and the combination of these personality traits is predictable for youth risk behavior (Obradović & Dinić, 2010). A study by Dinić et al (2016) indicated that two types of violent convicts may be identified on the basis of personality traits: a class of aggressive and a class of emotionally stable convicts. Reactive aggressiveness and neuroticism are higher in the class of violent aggressive convicts, whereas neuroticism is higher in the class of emotionally stable convicts, thus confirming the importance of neuroticism in adults and juveniles.…”
Section: Highlightsmentioning
confidence: 99%
“…Juvenile delinquents display high neuroticism and low conscientiousness (Kodžopeljić et al, 2014), and the combination of these personality traits is predictable for youth risk behavior (Obradović & Dinić, 2010). A study by Dinić et al (2016) indicated that two types of violent convicts may be identified on the basis of personality traits: a class of aggressive and a class of emotionally stable convicts. Reactive aggressiveness and neuroticism are higher in the class of violent aggressive convicts, whereas neuroticism is higher in the class of emotionally stable convicts, thus confirming the importance of neuroticism in adults and juveniles.…”
Section: Highlightsmentioning
confidence: 99%